Technological Embeddedness and Organizational Change - Volkoff, Olga; Strong, Diane M.; Elmes, Michael B. (Organization Science, 2007)
While various theories have been proposed to explain how technology leads to organizational change, in general they have focused either on the technology and ignored the influence of human agency, or on social interaction and ignored the technology. In this paper, we propose a new theory of technology-mediated organizational change that bridges these two extremes. Using grounded theory methodology, we conducted a three-year study of an enterprise system implementation. From the data collected, we identified embeddedness as central to the process of change. When embedded in technology, organizational elements such as routines and roles acquire a material aspect, in addition to the ostensive and performative aspects identified by Feldman and Pentland (2003). Our new theory employs the lens of critical realism because in our view, common constructivist perspectives such as structuration theory or actor network theory have limited our understanding of technology as a mediator of organizational change. Using a critical realist perspective, our theory explains the process of change as a three-stage cycle in which the ostensive, performative, and material aspects of organizational elements interact differently in each stage.